Observation of transition cascades in sheared liquid crystalline polymers. Issue 16 (2nd April 2020) - Fox, Ryan J.; Forest, M. Gregory; Picken, Stephen J.; Dingemans, Theo J.
Abstract : We observe anomalous shear thickening behavior of a lyotropic liquid crystalline polymer due to the dynamics of the nematic director. Abstract : We report on the shear rheology of liquid crystalline solutions composed of charged, rodlike polymers that form supramolecular assemblies dispersed in water. Under steady shear, we observe shear thickening behavior, followed by a hesitation in the viscosity accompanied by an extremely narrow range of negative first normal stress difference. The Peclet number (Pe, shear rate normalized by rod rotational diffusivity) for the onset of shear thickening is in agreement with previous, high-resolution numerical simulations of the Doi–Edwards–Hess kinetic theory. We interrogate these dynamic responses through shear step-down experiments, revealing a complex evolution of transient responses. Detailed analysis of the stress transients provides compelling evidence that the principal axis of the rod orientational distribution, the nematic director, undergoes a cascade of transitions and coexistence of periodic states known as kayaking, tumbling, and wagging, before transitioning to steady flow alignment above a critical shear rate.